2006
DOI: 10.1159/000095596
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High Extracellular Potassium on IKr Inhibition by Anti-Arrhythmic Agents

Abstract: Background: Hyperkalemia is a potentially life-threatening disorder frequently occurring in hospitalized patients. The ischemic myocardium releases potassium into the extracellular space which can cause regional hyperkalemia. These changes may modify the effects of anti-arrhythmic drugs acting on the rapid component of the delayed rectifier potassium current (IKr). We evaluated the influence of increased extracellular potassium concentration [K+]e on IKr inhibition by amiodarone, azimilid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Our previous studies have demonstrated that for IKr-blocking antiarrhythmic drugs like azimilide, quinidine and dofetilide, their HERG-inhibitory effect decreases with extracellular acidosis and hyperkalemia [14, 15]. These antiarrhythmic drugs have been noted for their proarrhythmic toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies have demonstrated that for IKr-blocking antiarrhythmic drugs like azimilide, quinidine and dofetilide, their HERG-inhibitory effect decreases with extracellular acidosis and hyperkalemia [14, 15]. These antiarrhythmic drugs have been noted for their proarrhythmic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…TdP can develop in 3–4% of patients receiving dofetilide intravenously [28]. On the other hand, amiodarone exerts a similar degree of HERG inhibition despite the decreasing extracellular pH [14] or increasing extracellular potassium concentration [15]. The risk of developing TdP with amiodarone is regarded as very low compared to other antiarrhythmic drugs [29] (less than 1% [6]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When patients on I Kr -blocking antiarrhythmic drugs drink citrus juices, the additional I Kr inhibition by naringenin from the citrus juice may lead to excessive QT prolongation, and thus the risk of developing arrhythmias. This may be especially the case when the patient has metabolic and electrolyte disorders such as hypokalemia [16, 24], cardiac ischemia with resulting regional acidosis and hyperkalemia [25,26,27], or a congenital defect in the potassium channel [28]. …”
Section: Discussionmentioning
confidence: 99%
“…In MI patients, a prolonged QT correlates with an increased risk for arrhythmias and death [4] ; increased QT variability correlates with susceptibility to reentrant ventricular tachyarrhythmias [5] , and increased T-wave alternans correlates with an increased risk of sudden death following MI [6] . Indeed, at tissue level, repolarization dispersion correlates with an increased risk of arrhythmias, and this dispersion is noted when comparing ion channel behavior between normal and ischemic conditions [7,8] .…”
mentioning
confidence: 99%